Trends in emotional wellbeing during COVID-19 by ethnicity, age and gender: evidence from a higher education staff survey - Lotti, Lorenzo; Ragazzi, Isabella; Morrison Gutman, Leslie (Frontiers in Education, 2024)
This paper provides evidence of the trends in the emotional wellbeing of university staff during the COVID-19 pandemic, with a focus on differences according to age, gender and ethnicity. From June 2020 to July 2021 a survey was circulated to University College London staff, capturing information on self-described demographic indicators (age, gender, and ethnicity), satisfaction with academic life, and mental and emotional wellbeing. Results show a moderate level of emotional wellbeing overall, with scores increasing after lockdowns were lifted. Some significant heterogeneity within the demographic variables demonstrates the need for disaggregating the categories within Black and Minority Ethnic individuals. Black Caribbean and Black African staff reported higher levels of emotional wellbeing (respectively .60 and .81 higher wellbeing scores, on average) while staff who identified as Arab or 'other' reported lower levels (on average -1.0 and -.65) than staff who identified as White. There was a sharp increase in emotional wellbeing for Arab staff and a slight increase in Asian and 'other' ethnic staff. Findings from this research provide evidence into the trends in emotional wellbeing of faculty and staff in a United Kingdom university context, contributing to the literature focusing on higher education during the pandemic period. We also flag the importance of disaggregating Black and Minority Ethnic categorisation to describe and better understand the diverse impact on emotional wellbeing within different ethnic groups, which has rarely been explored in the literature assessing university staff wellbeing.